2014
DOI: 10.1177/0956462414530888
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies against Treponema pallidum among HIV-positive patients in a tertiary care hospital in Mexico

Abstract: Our objective was to determine the seroprevalence of syphilis among HIV-infected patients in a tertiary care hospital in Mexico City. A cross-sectional study was developed, and 318 HIV-positive patients were evaluated from January to February 2013 at Hospital de Infectología, National Medical Center 'La Raza' (a tertiary care hospital specialising in infectious diseases in Mexico City). Laboratory data were screened for the detection of antibodies against Treponema pallidum. Patients completed a questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…This data may be used as feedback to prevent and eradicate HIV/syphilis co-infection in the future. Syphilis seroprevalence in diagnosed HIV infected individuals was reported between 5.2-25% in other countries (16)(17)(18), although social, cultural and economic differences between countries may affect the frequency of STDs. Our study showed the magnitude and quality of HIV/AIDS-syphilis co-infection status for the first time in Turkey and revealed that syphilis co-infection prevalence in HIV/AIDS may be accepted as moderate level.…”
Section: Discussionmentioning
confidence: 99%
“…This data may be used as feedback to prevent and eradicate HIV/syphilis co-infection in the future. Syphilis seroprevalence in diagnosed HIV infected individuals was reported between 5.2-25% in other countries (16)(17)(18), although social, cultural and economic differences between countries may affect the frequency of STDs. Our study showed the magnitude and quality of HIV/AIDS-syphilis co-infection status for the first time in Turkey and revealed that syphilis co-infection prevalence in HIV/AIDS may be accepted as moderate level.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 350 000 adverse pregnancy outcomes worldwide occurred as a result of syphilis, including 143 000 early foetal deaths, 62 000 neonatal deaths, 44 000 preterm/low-birth-weight babies and 102 000 infected infants were reported globally [3]. Studies have also shown that Syphilis ulcers can facilitate the transmission of HIV up to 5 times among HIV infected patients [4], [5]. Several methods used for the detection of Syphilis such as microscopy and molecular technologies are currently available.…”
Section: Introductionmentioning
confidence: 99%
“…The HIV epidemic has exacted a severe toll on MSM, with HIV infections from 9.1% in 2009 to 23.3% in 2020 (2). In addition, the prevalence of HIV and syphilis co-infection has increased from 8% (Mexico, 2010(Mexico, -2018 to 25% (Turkey, 2013) (3,4). Previous studies have found that syphilis infections could potentially facilitate HIV transmission and increase the likelihood of acquiring HIV (5).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the global rates of substance abuse among men who have sex with men have increased dramatically. Evidence from European countries and China suggests that methamphetamine and ecstasy are the most popular drugs used by MSM in the past years (4)(5)(6). A recent study among 3,588 number of participants that explored drug use problems found that the use of nitrite inhalers have overtaken methamphetamine as the most popular substance abused among MSM (7).…”
Section: Introductionmentioning
confidence: 99%